USE OF TRANSFERRIN PLOYMORPHISM IN LEGAL MEDICINE AND PATERNITY DISPUTED CASES - D.D. Farhoud (Iranian Journal of Public Health, 1979)
This paper deals with the use of transferring (Tf) system in legal medicine and forensic serology. Biased upon the clear for mal genetics and excellent typing of Tf phenotypes, in case of rare Tf variants, favorable results are obtained in disputed paternity. In the present case of disputed paternity, the child and the father exhibits B2 C type while the mother shows the type CC. But the father objects to be the biological father of the child. Legally speaking, the child inherits the B2 band from the father. Since the B2 gene frequency is shown to be very .rare the possibility of having another person with a similar type, who could be assumed as a biological father I is very uncommon and unbelievable. Finally, because of the high frequency of homozygote Tf CC the use of Tf system in disputed Paternity is not always that successful, but if a variant, as found in the present case, is detected than the Tf system is more reliable interesting and useful.